2011
DOI: 10.1088/1478-3975/8/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

AFM stiffness nanotomography of normal, metaplastic and dysplastic human esophageal cells

Abstract: The mechanical stiffness of individual cells is important in tissue homeostasis, cell growth, division, and motility, and the epithelial-mesenchymal transition in the initiation of cancer. In this work, a normal squamous cell line (EPC2) and metaplastic (CP-A) as well as dysplastic (CP-D) Barrett’s Esophagus columnar cell lines are studied as a model of pre-neoplastic progression in the human esophagus. We used the combination of an atomic force microscope (AFM) with a scanning confocal fluorescence lifetime i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 38 publications
7
104
0
1
Order By: Relevance
“…Thus, due to the differences in microenvironments, cells derived from normal tissues and tumors are intrinsically different in their stiffness, which allows Young's modulus to be a reliable biomarker in the evaluation of metastasis and the motility of cells. In addition, the morphological observations support this opinion experimentally, showing that the cancerous cells usually have decreased stress fibers [25,29,33,67,68], increased cortical actin [25,33], and more lamellipodia [26,65], which benefit the invasion of cells by decreasing adhesion with the substrate and increasing the contraction forces for deformation and protrusion [27,64]. Taking into account that the nuclei are usually softer in cells with higher motility [58] and that the cortex actin network is much softer than the stress fibers [41], it is reasonable to detect a lower Young's modulus in metastatic carcinoma cells.…”
Section: Data Volumementioning
confidence: 63%
“…Thus, due to the differences in microenvironments, cells derived from normal tissues and tumors are intrinsically different in their stiffness, which allows Young's modulus to be a reliable biomarker in the evaluation of metastasis and the motility of cells. In addition, the morphological observations support this opinion experimentally, showing that the cancerous cells usually have decreased stress fibers [25,29,33,67,68], increased cortical actin [25,33], and more lamellipodia [26,65], which benefit the invasion of cells by decreasing adhesion with the substrate and increasing the contraction forces for deformation and protrusion [27,64]. Taking into account that the nuclei are usually softer in cells with higher motility [58] and that the cortex actin network is much softer than the stress fibers [41], it is reasonable to detect a lower Young's modulus in metastatic carcinoma cells.…”
Section: Data Volumementioning
confidence: 63%
“…The mechanical stiffness of individual cells is important in tissue homeostasis, cell growth, division and motility, and the epithelial-mesenchymal transition in the initiation of cancer [22]. In this study, we found that the rigidity of Treg cells from patients with GVHD were similar to Treg cells without GVHD by the detection of adhesion force.…”
Section: Resultsmentioning
confidence: 53%
“…This study may lunch further mechanism understandings and optimizations for prognosis and prevention of any blood-related disorders, particularly on diagnosis and profiling the inflammatory modifications at different degrees level. Beyond imaging, AFM provides a "real time" study of living organisms, emerging multifunctional application tools such as: morphology, molecular forces 19,20 and mechanical properties 32,33 . However, AFM requires the immobilization of the cells on bare surfaces, which may influence the cell morphology 34 .…”
Section: Discussionmentioning
confidence: 99%
“…By isolating, immobilizing and washing the cells in one step, we significantly shorten the time for sample preparation, which does not exceed 5 minutes. Even the following measurements on AFM can require longer time and expertise at the beginning, for diagnostic purpose a fully automatic system to analyse cell 21 can be combined and developed 32,33 . Currently, the clinical diagnostic is based on the morphology of the cells, stained with specific antibodies, using conventional microscopic techniques.…”
Section: Discussionmentioning
confidence: 99%